Surveillance on ESBL-Escherichia coli and Indicator ARG in Wastewater and Reclaimed Water of Four Regions of Spain: Impact of Different Disinfection Treatments - Márcia Oliveira; Pilar Truchado; Rebeca Cordero-García; María I. Gil; Manuel Abellán Soler; Amador Rancaño; Francisca García; Avelino Álvarez-Ordóñez; Ana Allende (MDPI AG, 2023)
In the present study, the occurrence of indicator antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) both in the influent and the effluent of four Spanish wastewater treatment plants (WWTPs) was monitored for 12 months, and the susceptibility profiles of 89 recovered extended spectrum β-lactamase (ESBL)-producing Escherichia coli isolates were obtained against a wide range of antimicrobials. The aim of the study was to better understand whether the current wastewater treatment practices allow us to obtain safe reclaimed water mitigating the spread of ARB and ARGs to the environment. Results showed high concentrations of ESBL-producing E. coli as well as a high prevalence of a range of ARGs in the influent samples. The reclamation treatments implemented in the WWTPs were effective in reducing both the occurrence of ESBL E. coli and ARGs, although significant differences were observed among WWTPs. Despite these reductions in occurrence observed upon wastewater treatment, our findings suggest that WWTP effluents may represent an important source of ARGs, which could be transferred among environmental bacteria and disseminate antimicrobial resistance through the food chain. Remarkably, no major differences were observed in the susceptibility profiles of the ESBL E. coli isolated from influent and effluent waters, indicating that water treatments do not give rise to the emergence of new resistance phenotypes.